Cannabidiol, among Other Cannabinoid Drugs, Modulates Prepulse Inhibition of Startle in the SHR Animal Model: Implications for Schizophrenia Pharmacotherapy - Peres, Fernanda F.; Levin, Raquel; Almeida, Valéria; Zuardi, Antonio W.; Hallak, Jaime E.; Crippa, José A.; Abilio, Vanessa C. (Frontiers in Pharmacology, 2016)
Schizophrenia is a severe psychiatric disorder that involves positive, negative and cognitive symptoms. Prepulse inhibition of startle reflex (PPI) is a paradigm that assesses the sensorimotor gating functioning and is impaired in schizophrenia patients as well as in animal models of this disorder. Recent data point to the participation of the endocannabinoid system in the pathophysiology and pharmacotherapy of schizophrenia. Here, we focus on the effects of cannabinoid drugs on the PPI deficit of animal models of schizophrenia, with greater focus on the SHR (Spontaneously Hypertensive Rats) strain, and on the future prospects resulting from these findings.